Rethinking Greek Capitalism through the Lens of Industrial Relations Reform: A View until the 2015 Referendum - Wood, Geoffrey; Szamosi, Leslie; Psychogios, Alexandros; Sarvanidis, Sofoklis; Fotopoulou, Dialechti (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2015)
Although the literature on comparative capitalism has been expanded to encompass the Mixed Market Economies (MMEs) of the Mediterranean world and other less mature institutional arrangements, it can be argued that more attention needs to be accorded to internal diversity within capitalist archetypes and the nature and path of change. In focusing on the latter, this paper explores changes in Industrial relations (Ir) regulation and practice in Greece which, since the onset of the economic crisis, has shifted towards lighter regulation; however, liberalization has not meant convergence with the mature Liberal Market Economy (LME) model and its presumed associated complementarities. Based on current developments and advances in the literature on comparative capitalism, this study explores the process and dynamics of institutional change, and the long continuities that set Greece apart from both ‘disorganized’ LMEs and other MMEs. This encompasses issues such as the composition of elites, the nature of institutional path dependence and change, and the uneven and partial nature of what constitutes institutional functionality. Whilst the Greek system is commonly condemned as dysfunctional, it satisfies specific economic interests. Being impelled in one direction by a progressive movement from below, it is driven in another by external pressures, and, at home, by “unpatriotic” elites, who have little interest in stronger regulation, and may well be served by weaker governmental capabilities. As local economic elites seek to reposition themselves within the system in order to cope with shifts in the capitalist economy, it may result in them further narrowing their focus onto their own immediate concerns accommodated through economic liberalization. Smaller, marginal, players may be pushed further out of the system and/or actively choose to withdraw, the attempts of the present government to ameliorate the shocks of liberalization notwithstanding. This vests the organized labour and other civil society associations with great historic importance.